Modularity in the design of reconfigurable manufacturing systems. Issue 1 (July 2017) - Lameche, Khaled; Najid, Najib M.; Castagna, Pierre; Kouiss, Khalid
Abstract: According to recent results, Reconfigurable Manufacturing Systems or RMSs are the most efficient for manufacturing companies to adapt to the current market. This market is characterized by a high competitive level and very frequent and sudden variations in customer demands. Developing an RMS is not an easy task and a lot of work has been done in both academic and industrial fields to give solutions to address this issue. We can, for example, apply different methods and techniques used in the design of complex systems to design an RMS, these methods should be studied, analyzed, modified and improved if necessary before to be applied. Modularity is one of these techniques. In this paper, we will discuss how modularity could be used to develop RMS, and we will propose a standard approach based on the Design Structure Matrix to design an RMS with a modular architecture.